Pengaruh Penerapan Sistem Pengendalian Internal Pemerintah Dan Kompetensi Sumber Daya Manusia Terhadap Pencegahan Kasus Fraud / Kecurangan Akuntansi Dengan Pendekatan Fraud Hexagon (Studi Kasus Pada Pemerintah Provinsi Sumatera Utara) - Gita Ayu Pratama; Nur Ahmadi Bi Rahmani; Kusmilawaty Kusmilawaty (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine the effect of implementing the Government's Internal Control System and Human Resource Competency on preventing cases of accounting fraud / fraud using the Fraud Hexagon Approach (Case Study of the North Sumatra Provincial Government). The research method used is a survey method by distributing questionnaires to respondents consisting of government employees involved in internal control processes and accounting activities. The questionnaire measures the level of implementation of the government's internal control system, human resource competency, and cases of accounting fraud that occur. The Fraud Hexagon approach is used to analyze factors that influence fraud prevention. This research uses quantitative methods, primary data collection techniques by distributing questionnaires. The population and sample were 50 respondents and used a total saturated sampling technique. This research uses SPSS statistical tools. Data were analyzed using multiple regression analysis method. The results of this research show that the implementation of the Internal Control System has a positive and significant effect on preventing accounting fraud cases. Human Resource Competency has a positive and significant effect on preventing accounting fraud cases. And the F test shows that the Implementation of the Internal Control System and Human Resource Competency has a simultaneous and significant positive effect on the Prevention of Accounting Fraud Cases.